Propuesta de adaptación del documento ASCE/SEI31-03 “Evaluación Sísmica De Edificaciones Existentes” - López Palomino, Paulo Marcelo (Escuela Colombiana de Ingeniería Julio Garavito, 2014)
This document presents a proposal to adapt the standard ASCE / SEI31-03 "Seismic Evaluation of Existing Buildings" of the American Society of Civil Engineers, to provide an evaluation methodology of existing buildings in Colombia. This methodology contains the evaluation procedure of buildings of various structural systems with materials such as: wood, masonry, steel and reinforced concrete; it also determines and progressively analyzes, and with incremental complexity, the possible deficiencies presented by structural, non-structural elements, foundations and geological risks, through the evaluation of resistance, rigidity, structural configuration and basic details of ductility. In this way, there will be tools for choosing the rehabilitation procedure based on the improvement of the seismic performance of the building. Considering that in Colombia the existing information for evaluation and subsequent seismic rehabilitation does not provide a prescriptive orientation to evaluate the existing constructions, it is necessary to contribute to the enrichment of the elements contained in the Colombian earthquake-resistant construction regulation -NSR-10- through a proposal to adapt document ASCE / SEI31-03 "Seismic Assessment of Existing Buildings"

En este documento se presenta una propuesta de adaptación de la norma ASCE/SEI31-03 “Seismic Evaluation of Existing Buildings” de la American Society of Civil Engineers, para proporcionar una metodología de evaluación de edificaciones existentes en Colombia. Dicha metodología contiene el procedimiento de evaluación de edificaciones de diversos sistemas estructurales con materiales como: madera, mampostería, acero y concreto reforzado; también determina y analiza progresivamente y con complejidad incremental las posibles deficiencias que presentan los elementos estructurales, no estructurales, cimentaciones y riesgos geológicos, a través de la evaluación de la resistencia, rigidez, configuración estructural y detalles básicos de ductilidad. De esta manera se contará con herramientas para la elección del procedimiento de rehabilitación en función del mejoramiento del desempeño sísmico de la edificación. Considerando que en Colombia la información existente para realizar evaluación y posterior rehabilitación sísmica no proporciona una orientación prescriptiva para evaluar las construcciones existentes, es necesario contribuir al enriquecimiento de los elementos que contiene el reglamento colombiano de construcción sismo resistente -NSR-10- a través de una propuesta de adaptación del documento ASCE/SEI31-03 “Evaluación Sísmica de Edificaciones Existentes”
Keywords: Evaluación Sísmica; Rehabilitación Sísmica; Vulnerabilidad Sísmica; Edificaciones Existentes; Edificios - Efectos sísmicos; Buildings - Earthquake effects; Seismic Vulnerability; Seismic Rehabilitation; Seismic evaluation; Existing buildings